Comparison of FFT, AR and wavelet methods in transcranial doppler signal obtain from intracerebral vessels - Güler, I.; Hardalaç, F.; Erol, F.S. (My University, 2001)
In this work, transcranial Doppler signals recorded from the temporal region of brain on 35 patients were transferred to a personal computer (PC) via 16 bit sound card. FFT, AR and WT methods were applied to transcranial Doppler for obtaining sonograms. Spectral analysis were obtained in order to compare with three methods in the case of medical diagnosis. The comparison shows that WT method often better results for the spectral resolution than the other methods. This leads the determination of brain pressure more accurately.
Keywords: Sonogram; Temporal region; Transcranial doppler